2017
DOI: 10.1177/1099636217727145
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption in aluminium honeycomb cores reinforced with carbon fibre reinforced plastic tubes

Abstract: The energy-absorbing behaviour of an aluminium honeycomb core reinforced with unidirectional and woven carbon fibre reinforced plastic composite tubes has been investigated experimentally at quasi-static rates of strain. Small diameter carbon fibre reinforced plastic tubes, with chamfered ends, were inserted into the cells of an aluminium honeycomb in order to yield a lightweight energy-absorbing material. The resulting data are compared with crushing tests on arrays of free-standing composite tubes, supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…These observations are in agreement with previous work on unidirectional and woven composite tubes. 25
Figure 8.Load–displacement graphs following crushing tests on the [0°, 90°] s , [0°,+45°, −45°, 0°] and [0°] 4 core structures.
…”
Section: Resultsmentioning
confidence: 99%
“…These observations are in agreement with previous work on unidirectional and woven composite tubes. 25
Figure 8.Load–displacement graphs following crushing tests on the [0°, 90°] s , [0°,+45°, −45°, 0°] and [0°] 4 core structures.
…”
Section: Resultsmentioning
confidence: 99%
“…Relatively, for HLS and HLM structures, the SEA value increase from 10.9 kJ/kg to 11.5 kJ/kg. However, the SEA values from single to multiple tube reinforced foam structure did not vary significantly due to the influence of the initial mass of the structure as it is inversely proportional to the SEA value, as proposed by Alantali et al [ 16 ]. Invariably, the bamboo structures always dominated in any cases.…”
Section: Resultsmentioning
confidence: 77%
“…Recently, there has been growing interest in the possibility of using energy-absorbing tubes as core materials in sandwich structures [2730]. Xiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Alantali et al. [29] studied the effect of reinforcing an aluminium honeycomb core with small composite tubes on energy-absorption under quasi-static loading. Here, it was shown that a significant enhancement in SEA could be achieved by incorporating composite tubes into the honeycomb core.…”
Section: Introductionmentioning
confidence: 99%